PEMBERIAN EDUKASI KESEHATAN RAMBUT DAN KULIT KEPALA PADA PENGHUNI RUMAH YATIM AR-RAHMAH BANJARBARU KALIMANTAN SELATAN - Ratna Restapaty; Rahmi Hidayati; Putri Indah Sayakti (Journal of Science and Social Development, 2019)
Hair is a crown for everyone who grows on the head. Many things are often experienced by people related to the scalp. Sometimes scalp problems are often considered trivial by most people. Among the scalp problems that are often experienced are dandruff. In addition to the problem of dandruff, lice growth is a hair health factor that is often found. The orphanage as a place of residence with dense environmental characteristics and lack of knowledge, attitudes of orphanage children to the risk of infection, fungal transmission of the scalp and the development of lice. The problems in the Orphanage environment are a challenge as well as an opportunity to provide education related to hair and scalp health. The purpose of this activity itself is to improve the attitude of healthy living by providing knowledge about maintaining healthy scalp free of dandruff and lice free hair health in a dense environment. The implementation method used is the provision of education related to hair and scalp health and proper hair washing tutorials. The results of the implementation achieved were the residents of the orphanage knowing what causes dandruff and head lice. And knowing how to maintain cleanliness of the head, especially on hair and scalp.